Pinhole SPECT of mice using the LumaGEM gamma camera - MacDonald, L.R.; Patt, B.E.; Iwanczyk, J.S.; Tsui, B.M.W.; Wang, Y.; Frey, E.C.; Wessell, D.E.; Acton, P.D.; Kung, H.F. (IEEE transactions on nuclear science, 2001)
LumaGEM is a newly developed gamma camera for dedicated, small field of view, high spatial resolution imaging. The system consists of an array of 2/spl times/2/spl times/6 mm/sup 3/ NaI(Tl) pixels coupled to an array of position-sensitive photomultiplier tubes. It has a 125/spl times/125 mm/sup 2/ field of view. A pinhole collimator was used on LumaGEM to acquire SPECT images of mice that had transgenic modifications so as to model various diseases. Pinhole apertures of 1, 2 and 3 mm are interchangeable on the collimator and were used to acquire images. An iterative MLEM algorithm for pinhole SPECT was used to reconstruct the 128 projection images that covered 360/spl deg/ rotation. The reconstruction algorithm is based on a projector and backprojector pair implemented using a ray-tracing algorithm. The crucial reconstruction input parameters are the radius of rotation, center of rotation, and pinhole focal length. Ideal pinhole geometry is assumed, and no correction for attenuation has been made. The preliminary images presented here show detailed uptake in the mice subjects and are a convincing sign that animal SPECT can reach submillimeter spatial resolution and be a valuable tool in the study of diseases and the development of pharmaceuticals in animal models.